ANALYSIS OVER HUMAN RESOURCES INFORMATION SYSTEM IMPLEMENTATION WHICH INFLUENCED COMPETENCE AND MOTIVATION IN IMPROVING EMPLOYEE PERFORMANCE AT ONE OF MINERAL MINING AND COAL CONTRACTOR COMPANY - Farahdiba, Syifa; Lenny C. Nawangsari (Dinasti Publisher, 2020)
This research has purpose to find out and investigated the role of HRIS implementation, motivation and competence to improve the employees performance at PT. Artamulia Tatapratama. The research method used quantitative methods with causality approach. The population and sample were amounted to 190 employees. Data were analyzed using structural equation modeling (SEM). And This research was revealed that 1) HRIS implementation had significant beneficial impact towards employee performance, 2) Motivation had significant positive effect on employee performance, 3) Competence had a remarkable reaction over employee performance, 4) HRIS implementation had significant beneficial influence towards motivation and 5) HRIS implementation had significant positive reaction to competence.